Wave Energy Conversion Efficiency of the UGEN along the Western Portuguese Coast (Proceedings of the European Wave and Tidal Energy Conference, 2025)
An assessment for Portugal continental coast of the Levelized Cost of Energy (LCOE) of a floating Wave Energy Converter (WEC) called UGEN is presented in this article. The UGEN device is composed by two well-known components: an asymmetric floater and the Wells turbine, which is activated by the reversible air flow driven by the U-shaped Oscillating Water Column (OWC). The motion of the U-shaped OWC, mainly induced by the rolling of the floater, forces the air through the duct where a Wells turbine is installed to absorb the wave energy.